Irigenin reduces the expression of caspase-3 and matrix metalloproteinases, thus suppressing apoptosis and extracellular matrix degradation in TNF-α-stimulated nucleus pulposus cells. (1st November 2021) - Zhang, Gaofeng; Liao, Yuanmei; Yang, Hanshi; Tao, Jian; Ma, Lin; Zuo, Xiaohua
Abstract: Irigenin, an isoflavonoid isolated from the rhizome of Belamcanda chinensis, possess various pharmacological effects. However, the effect and mechanism of irigenin on intervertebral disc degeneration (IDD) remain unclear. The potential targets of irigenin or disease were predicted using PharmMapper or GeneCards databases, respectively. The overlapping targets were inputted into the String database to establish protein-protein interaction (PPI) network. The overlapping targets were also submitted to DAVID webserver to perform gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. Nucleus pulposus (NP) cells were exposed to 10 ng/mL tumor necrosis factor-α (TNF-α) to establish a cell model of IDD. Cell viability, LDH content, apoptosis and caspase-3 activity were evaluated by CCK-8, LDH release, TUNEL, and caspase-3 activity assays, respectively. The expression of collagen II, aggrecan, matrix metalloproteinase (MMP)-2, MMP-3, MMP-9, and MMP-13 were detected by qRT-PCR and western blot analyses. The network analysis revealed that MMP-2, MMP-3, MMP-9, MMP-13, caspase-3 (CASP3), vitamin D receptor (VDR), insulin-like growth factor 1 (IGF1), and transforming growth factor beta2 (TGFB2) play key roles in the effect of irigenin against IDD. TNF-α stimulation inhibited cell viability and increased LDH content, apoptosis, caspase-3 expression and caspase-3 activity in NP cells, which were reversed by irigenin treatment. TNF-α stimulation inhibited the expression of collagen II and aggrecan and upregulated MMPs (MMP-2, MMP-3, MMP-9, and MMP-13) in NP cells, while such changes were abolished by irigenin treatment. In conclusion, irigenin suppressed apoptosis and ECM degradation in TNF-α-stimulated NP cells by reducing the expression of caspase-3 and MMPs. Highlights: MMP-2, MMP-3, MMP-9, MMP-13, CASP3, VDR, IGF1 and TGFB2 are identified as the potential target genes of irigenin against IDD. TNF signaling pathway is identified as an important pathway in the treatment of IDD using irigenin. Irigenin inhibits TNF-α-induced apoptosis in NP cells via inhibiting caspase-3 expression. Irigenin protects NP cells against TNF-α-induced ECM breakdown via blocking the expression of MMPs.